A temporal sequence of thalamic activity unfolds at transitions in behavioral arousal state - Setzer, Beverly; Fultz, Nina E.; Gomez, Daniel E. P.; Williams, Stephanie D.; Bonmassar, Giorgio; Polimeni, Jonathan R.; Lewis, Laura D. (Nature communications, 2022)
Awakening from sleep reflects a profound transformation in neural activity and behavior. The thalamus is a key controller of arousal state, but whether its diverse nuclei exhibit coordinated or distinct activity at transitions in behavioral arousal state is unknown. Using fast fMRI at ultra-high field (7 Tesla), we measured sub-second activity across thalamocortical networks and within nine thalamic nuclei to delineate these dynamics during spontaneous transitions in behavioral arousal state. We discovered a stereotyped sequence of activity across thalamic nuclei and cingulate cortex that preceded behavioral arousal after a period of inactivity, followed by widespread deactivation. These thalamic dynamics were linked to whether participants subsequently fell back into unresponsiveness, with unified thalamic activation reflecting maintenance of behavior. These results provide an outline of the complex interactions across thalamocortical circuits that orchestrate behavioral arousal state transitions, and additionally, demonstrate that fast fMRI can resolve sub-second subcortical dynamics in the human brain. How the brain transitions between sleep and wakefulness is not well understood. Here, the authors discover that a sequence of activity unfolds across the thalamus before transitions from unresponsiveness to active behavior.